DEVELOPMENT OF INTERACTIVE MULTIMEDIA BASED ON CONTEXTUAL TEACHING AND LEARNING ON THEME 6 MY GOALS SUB-THEME 1 ME & MY DREAMS CLASS IV SD NEGERI 106789 TANJUNG GUSTA - Lasmaria Agnes Sinaga; Hidayat Hidayat; R. Mursid R. Mursid (SENSEI RESEARCH CENTER, 2021)
This research and development aim to 1) develop interactive multimedia based on Contextual Teaching and Learning on the theme 6 my ideals, subtheme 1 I & my dreams in the fourth grade of SD Negeri 106789 Tanjung Gusta; (2) the position of interactive multimedia based on Contextual Teaching and Learning on the theme 6 my goals, sub-theme 1 I & my dreams in the fourth grade of SD Negeri 106789 Tanjung Gusta; (3) Knowing the effectiveness of interactive multimedia based on Contextual Teaching and Learning on theme 6 my ideals sub-theme 1 I & my dreams in improving student learning outcomes in grade IV SD Negeri 106789 Tanjung Gusta. The development model in this research is 4D which consists of 4 stages, namely: define, design, develop, and distribute. The results showed that: (1) the expert's assessment of multimedia content/materials was in very decent criteria with an average score (4.58); (2) the expert's assessment of multimedia construction is in very decent criteria with an average score (4,62); (3) the assessment of instructional design experts is in the very feasible criteria with an average score (4,43). Moreover, it is effectively used to improve student learning outcomes, including the percentage of classical completeness in the first trial reaching 80% with an average N-Gain acquisition of 0.5 and the classical mastery percentage in the second trial reaching 100%, with the average N-Gain acquisition being 0.8 and received a positive response from the teacher reaching an average of 3.4 with very decent criteria